2005
DOI: 10.1071/ch05188
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 1-[(3-Trifluoromethyl)phenyl]-3,4-dihydro-2(1H)-pyridinone Derivatives from Aza Annulation Reactions of N-[(3-Trifluoromethyl)phenyl]-Substituted Enaminones

Abstract: Reaction of 3-trifluoromethylaniline with the 1,3-diketones 1a–1c and 5a–5d affords the N-[(3-trifluoromethyl)phenyl]-substituted enaminones 2a–2c and 6a–6d. Reaction of 2a with the acryloyl chloride derivatives 3a–3c gives the 1-[(3-trifluoromethyl)phenyl]-3,4-dihydro-2(1H)-pyridinones 4a, 4c, 4d; in a similar manner the 2(1H)-pyridinone 4b is obtained from 2b. Reaction of 6c, 6d with acryloyl chloride affords the 2,5(1H,3H)-quinolinedione derivatives 7 and 9 together with the acrylamides 8a, 8b. The 2(1H)-py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…We also report that dimethylacetylenedicarboxylate (DMAD) inserts into the C−H bond of the β-enaminone substituent instead of into the C−Pd bond. The attack of DMAD on various β-enaminones has been reported recently. , In addition, we have found that the resulting complex inserts an isocyanide into the Pd−C bond, which, in turn, undergoes a photooxygenation process giving rise to an unprecedented palladium pincer derivative and acetic acid.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…We also report that dimethylacetylenedicarboxylate (DMAD) inserts into the C−H bond of the β-enaminone substituent instead of into the C−Pd bond. The attack of DMAD on various β-enaminones has been reported recently. , In addition, we have found that the resulting complex inserts an isocyanide into the Pd−C bond, which, in turn, undergoes a photooxygenation process giving rise to an unprecedented palladium pincer derivative and acetic acid.…”
Section: Introductionsupporting
confidence: 57%
“…The insertion of dimethylacetylenedicarboxylate into aliphatic C(sp 2 )−H bonds has been previously found to occur in β-enaminones, affording the corresponding esters instead of the expected [4+2] cycloaddition products . More recently this reaction, which is said to take several days at room temperature, has proved to be general .…”
Section: Resultsmentioning
confidence: 94%
“…It is worth mentioning that when ( Z )-4-(cyclohexylamino)pent-3-en-2-one 1k and diethyl but-2-ynedioate 2b were subjected to the optimized reaction conditions, an unexpected compound 4a was isolated in 78% yield, and the desired pyrroles 3kb could be successfully obtained in 52% yield at the 120 °C for 8 h (Scheme ). So the compound 4a would be the intermediate of the transformation.…”
mentioning
confidence: 99%
“…Ali and Winzenberg [11] have similarly explored annulation chemistry to prepare a range of potential biologically active materials based on a substituted 3,4-dihydropyridin-2(1H)-one motif.…”
Section: Tom Spurling Joined the Csiro Division Of Applied Chemistry mentioning
confidence: 99%
“…[8] The papers by Liepa, Nguyen, and Saubern, [9] Johnson and Turner, [10] Ali and Winzenberg, [11] and Savage and Wernert [12] illustrate how CSIRO is continuing to meet this challenge. There is a particular focus on heterocyclic chemistry in CSIRO, and Australia generally, in the production of chemical diversity.…”
Section: Tom Spurling Joined the Csiro Division Of Applied Chemistry mentioning
confidence: 99%